Lignocellulosic Biomass for the Synthesis of Nanocellulose and Its Eco-Friendly Advanced Applications - Gupta, Guddu Kumar; Shukla, Pratyoosh (Frontiers in Chemistry, 2020)
Nanocellulose is a unique and natural compound extracted from native cellulose using different extraction techniques. Currently, nanocellulose has attracted attention due to its tremendous properties such as special surface chemistry, excellent physical and chemical strength, and rich hydroxyl group for modification. In addition, its significant biological properties like biodegradability, biocompatibility and non-toxicity accompanied by being environmentally friendly are added advantages. The current review is focused on the lignocellulosic biomass processing methods for the nanocellulose production and their usage for eco-friendly as well as environmental sustainability. We have also described the insights on different techniques by which cellulosic materials can be changed into cellulose nanofibers (CNFs), and cellulose nanocrystals (CNCs). Lastly, we further discussed how nano-cellulosic materials being used in a variety of applications such as the food sector, biomedical hygiene products, health care, water purification, and sensors. In the review envisages the unique uses of nanocelluloses in the production of nanocomposite materials like flexible supercapacitor and polymer matrix towards minimizing the utilization of global fossil energy and environmental pollution. Finally, the significant application of nanomaterials in the area of packaging industries, health and hygienic sector, cosmetics and other important sectors. In the aspects of techno-economically feasibility, nano-cellulose based materials may prove to be outstanding, environment friendly and mitigate the effluent load.